Cerebrospinal fluid levels of phosphorylated tau and Aβ1-38/Aβ1-40/Aβ1-42 in Alzheimer's disease with PS1 mutations. (June 2013) - Ikeda, Masaki; Yonemura, Kimie; Kakuda, Satoko; Tashiro, Yuichi; Fujita, Yukio; Takai, Eriko; Hashimoto, Yukiko; Makioka, Kouki; Furuta, Natsumi; Ishiguro, Koichi; Maruki, Risa; Yoshida, Jun'ichi; et al.
Abstract We studied seven cases of Alzheimer's disease (AD). Six of the patients had presenilin 1 (PS1) mutations (PS1AD). Three novel PS1 mutations (T99A, H131R and L219R) and three other missense mutations (M233L, H163R and V272A) were found in the PS1AD group. We measured the levels of phosphorylated tau (ptau-181, ptau-199) and Aβ (Aβ1-42, Aβ1-40 and Aβ1-38) in the cerebrospinal fluid (CSF) of PS1AD patients, early-onset sporadic AD (EOSAD), late-onset sporadic AD (LOSAD) and non-demented subjects (ND). The CSF levels of Aβ1-42 in the three AD groups were significantly lower than those of the ND group (p < 0.0001). CSF levels of Aβ1-42 in the PS1AD group were significantly lower than those in the two sporadic AD groups. The Aβ1-40 and Aβ1-38 levels in the CSF of the PS1AD group were significantly lower than those of the three other groups (p < 0.0001, respectively). The levels of Aβ1-40, Aβ1-38 and Aβ1-42 in the CSF of the PS1AD group remained lower than those of the ND group for 4 years. Not only CSF Aβ1-42, but also Aβ1-40 and Aβ1-38 decreased in the advanced stages of PS1AD.